Effect of CDC 2006 Revised HIV Testing Recommendations for Adults, Adolescents, Pregnant Women, and Newborns on State Laws, 2018. (July 2020) - Salvant Valentine, Sheila; Caldwell, Joseph; Tailor, Amrita
In 2006, the Centers for Disease Control and Prevention updated its recommendations for HIV testing of 4 population groups in health care settings: adults, adolescents, pregnant women, and newborns. Important components of the revised recommendations included opt-out routine HIV screening; eliminating prevention counseling for opt-out routine HIV screening; repeat HIV testing in the third trimester for all women at high risk for acquiring HIV and for women receiving health care in facilities and/or jurisdictions with high HIV burden; testing during labor and delivery for women with undocumented HIV status; and testing the newborn when the mother's HIV status is unknown. To assess the integration of these testing recommendations into state laws and to inform future recommendations, we researched and assessed statutes and regulations that addressed HIV testing in the 4 population groups in all 50 states and the District of Columbia in 2018. We then classified the laws, based on their consistency with the recommendations for each of the 4 population groups. Of 31 states and the District of Columbia that had relevant laws, all addressed at least 1 component of the recommendations. Although no state had laws that incorporated all the recommendations for all the population groups, 5 states (Delaware, Illinois, Louisiana, Maryland, and New Hampshire) had incorporated all the recommendations for adults and adolescents, and 4 states (Connecticut, Nevada, North Carolina, and West Virginia) had incorporated all the recommendations for pregnant women and newborns.